Synthesis and morphology investigations of a novel alkyne‐functionalized diblock copolymer. Issue 1 (9th October 2012) - Wei, Xinyu; Gu, Weiyin; Li, Le; Shen, Xiaobo; Kim, Jung‐Keun; Russell, Thomas P.
Abstract We reported the synthesis and morphology of a novel alkyne‐functionalized diblock copolymer (di‐BCP) poly(methyl methacrylate‐random‐propargyl methacrylate)‐block‐poly(4‐bromostyrene). The di‐BCPs were synthesized by atom transfer radical polymerization and postpolymerization deprotection, with good control over molecular weight and polydispersity index. Microphase separation in bulk di‐BCPs was confirmed by thermal analysis, small‐angle X‐ray scattering, and transmission electron microscopy. Microphase‐separated morphologies were also observed in thin films, and the orientation of the microdomains can be conveniently controlled by annealing under different solvents. © 2012 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2012